A rare case of male breast ductal carcinoma in-situ associated with prolactinoma. (1st September 2011) - Mallawaarachchi, Chandike Maithri; Ivanova, Snezana; Shorthouse, Alice; Shousha, Sami; Sinnett, Dudley
Abstract : A case of ductal carcinoma in-situ (DCIS) associated with prolactinoma in a male patient is described. A 56-year-old gentleman presented with lethargy and loss of libido. His prolactin at presentation was 3680 mU/l and an MRI scan of the head revealed a pituitary tumour suggestive of prolactinoma. Following 18 months of treatment with cabergoline, the prolactin level reduced to 914 mU/l. However, 3 years later he presented with blood stained nipple discharge, the cytology of which was negative for cancer. Ultrasound scan of his right breast revealed a single dilated mammary duct. Microdochectomy was performed. The histology revealed incompletely excised DCIS. There is increasing evidence of prolactinoma associated with breast cancer with or without DCIS in females. A review of the literature reveals only one previous case report of this association in males. This is the first case of pure DCIS preceded by prolactinoma in a male patient.